Factors Causing Claims Not Eligible to Pay Covid-19 Patients at the Imelda Workers General Hospital Indonesia in 2021 - Theresia Hutasoit; Callis Dewi Pancarani (Sean Institute, 2023)
Hospitals that provide Covid-19 services can apply for reimbursement of service fees to the Ministry of Health. However, if a discrepancy is found in the administration or service, the claim can be declared unfit to pay which can have an impact on reimbursement of the costs of services that have been provided to the patient. Claims that are not eligible to pay are claims that have been verified by the hospital but do not meet the provisions of both administration and service so that they cannot be paid. The purpose of this study was to find out the factors that caused claims that were not eligible to pay for Covid-19 patients at Imelda Workers Indonesia Hospital in 2022. This type of research was qualitative with a population of 18 claims and the sampling technique used was saturated sampling. The research instruments used were interview guidelines and checklist sheets. The method of data collection is done by observation and interviews. The results of the study obtained that the claim files of Covid-19 inpatients for the period June to September were 286 claims and the number of claims that were not eligible to pay was 18 claims. The factors that cause claims that are not eligible to pay are the criteria for Covid-19 patients not in accordance with the provisions, comorbid diagnoses that are not in accordance with the provisions, incomplete claim documents, supporting examinations that are not in accordance with the provisions and delays in claiming. The main cause of claims that are not eligible to pay for Covid-19 patients at Imelda Worker Indonesia Hospital is the delay in claims that have passed the date determined by the Ministry of Health. It is recommended that you pay more attention and be careful with the due date that has been determined by the Ministry of Health, so that there is no claim delay.